2018
DOI: 10.1051/e3sconf/20184002003
|View full text |Cite
|
Sign up to set email alerts
|

Hazards due to large wood accumulations: Local scour and backwater rise

Abstract: Large wood (LW) in rivers increases the flow variability and provides habitats for various species. During flood events, transported logs can accumulate at river infrastructures and increase the flood hazard. LW accumulations result in an upstream backwater rise and may increase local scour, for instance at bridge piers. Consequently, estimates of the resulting backwater rise and local scour are necessary to improve the flood hazard assessment. This study presents the findings of flume experiments with a movab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…(2014b) refer that LW pieces oriented parallel and oblique to the flow direction are transported in the line of maximum velocity in their original orientation. Schalko (2018) demonstrated that the deposition probability was six times lower for those pieces transported in parallel orientation with the flow direction. In the studied river reaches, the LW dimensions suggest the fast onset of LW transport; however, their prevailing orientation and log‐log and log‐living tree interactions in the channel and inundated floodplain may be limiting factors for long transport trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…(2014b) refer that LW pieces oriented parallel and oblique to the flow direction are transported in the line of maximum velocity in their original orientation. Schalko (2018) demonstrated that the deposition probability was six times lower for those pieces transported in parallel orientation with the flow direction. In the studied river reaches, the LW dimensions suggest the fast onset of LW transport; however, their prevailing orientation and log‐log and log‐living tree interactions in the channel and inundated floodplain may be limiting factors for long transport trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…Despite such benefits, trees that fall from forest slopes after heavy rainfall become LW that accumulates in rivers, posing hazards to people and property, e.g., [6]. LW disasters caused by heavy rainfall, occasionally accompanied by sediment-related disasters, have been reported in many countries [7][8][9]. In Japan, LW disasters occurred in Asakura City (Fukuoka Prefecture) and Hita City (Oita Prefecture) during heavy rainfall in 2017 in northern Kyushu [10], and in Hiroshima City and Kure City (both in Hiroshima Prefecture) during heavy rainfall in 2018 [11] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%